Amelioration of iodine supply is notably associated with thyroid function in healthy subjects and in patients with euthyroid Hashimoto’s thyroiditis - Nadja Novak; Ajda Biček; Katja Zaletel; Simona Gaberšček (Zdravniški Vestnik, 2016)
Background: Our aim was to establish how healthy subjects (HS) and patients with euthyroid Hashimoto's thyroiditis (EuHT) faced the increase in mandatory salt iodization in Slovenia in 1999 from previous 10 mg of potassium iodide to 25 mg per kg since data about thyroid function with respect to iodine supply are scant. Methods: In this retrospective study we reviewed records of 24,899 patients referred for the first time between 1995 and 2002 to our tertiary referral centre with a stable catchment area for more than 20 years. HS were negative and patients with EuHT positive for thyroid peroxidase antibodies and/or thyroglobulin antibodies. Thyrotropin (TSH), free thyroxine (fT4), and free triiodothyronine (fT3) levels were obtained. The fT4/fT3 ratio was calculated. Results: In the period 1995-1998, 917 HS had significantly lower fT4/fT3 ratio than 644 HS in the period 1999-2002 (2.6±0.6 and 2.9±0.9, respectively, p<0.001) on account of significantly higher fT3 (median 5.7 and 5.2 pmol/L, p<0.001). Similarly, in 1995-1998, 482 patients with EuHT had a lower fT4/fT3 ratio than 846 EuHT in 1999-2002 (2.4±0.6 and 2.8±0.7, respectively, p<0.001) on account of significantly higher fT3 (median 5.8 and 4.9, respectively, p=0.018). HS had a higher fT4/fT3 ratio than patients with EuHT in 1995-1998 but not in 1999-2002 (p<0.001 and p=0.206, respectively). Conclusions: Amelioration of iodine supply is associated with an increase in the fT4/fT3 ratio on account of lower fT3, and with a similar thyroid function in HS and in patients with EuHT.